Surface modification of ceramic materials using excimer lasers - Schubert, Emil; Bergmann, Hans Wilhelm (Surface Engineering, 1993)
In ceramics processing, the final machining steps for surface loaded devices have until now been mechanical in nature. Techniques such as turning or grinding, followed by finishing, lapping, honing, or polishing, are usually sufficient to produce the desired surface roughness. The lifetime of a ceramic component is in most cases determined by its surface features. Crack initiation often occurs at machining marks because the stress intensity factor of such defects results in higher stresses in the surface on loading. If these stresses exceed the material's strength, failure of the workpiece will occur. Depending on the actual conditions in service, various combinations of surface properties, e.g. roughness, coefficient of friction, or the absence of porosity, are required. Irradiating the surface with an excimer laser is a contact free, optical process that seals the surface with simultaneous smoothing and reduction in surface porosity. Results for laser treated alumina samples of different purities with as fired and diamond polished surface finishes are presented. The investigations show an improvement in both bending strength and Weibull modulus of the treated specimens.